Different mechanisms for E. coli disinfection and BPA degradation by CeO2-AgI under visible light irradiation - Mian Li; Fuyang Liu; Zhiyao Ma; Liu, Wen; Jialiang Liang; Meiping Tong (Chemical Engineering Journal, 2019)
CeO2-AgI, synthesized via depositing AgI nanoparticles onto CeO2 nanorods, was utilized for bacterial disinfection and organic contaminant degradation. Escherichia coli (E. coli) and Bisphenol A (BPA) were used as the model bacteria and emerging organic contaminant to test the photocatalytic activity of CeO2-AgI, respectively. Results showed that CeO2-AgI with the optimal AgI content exhibited superior photocatalytic activity over pure CeO2 or AgI for both inactivation of E. coli cells and BPA removal. However, the photocatalytic mechanisms for E. coli inactivation and BPA degradation were different. Specifically, the photo-generated holes (h+), photo-generated electrons (e−) and superoxide radicals (O2−) were the dominated active species for E. coli inactivation, whereas, BPA degradation relied on the generation of O2− and e−. Cell membrane disruption was found to be the main disinfection mechanism. The decomposition of BPA was clarified by detecting the degradation intermediates by LC–MS and DFT calculation. The facile synthesized CeO2-AgI exhibited good photocatalytic stability in four reused cycles and thus could be potentially applied to purify water.
Keywords: Bisphenol A; CeO-AgI; Disinfection; Photocatalysis; Reactive oxygen species; Reusability